1992
DOI: 10.1017/s0021859600071574
|View full text |Cite
|
Sign up to set email alerts
|

Ratios of strontium-85 to cations for crops and soils of Greece

Abstract: S U M M A R YIn a glasshouse pot experiment in Athens, Greece in 1989, 85 Sr to calcium observed ratios (OR) based on the values of exchangeable Ca instead of soil Ca (OR ex Ca), were determined for crops or plant parts grown in eight soils widely differing in their physical and chemical properties. Compared to the values of concentration ratio (CRs) the values of OR ex Ca did not show as wide variation with the soil type. They were relatively constant and usually not related to soil properties. The OR ex Ca … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…This question should be investigated additionally in more details. We think that the difference in the ratios strontium-calcium in plant and in the corresponding soil solution marked by Papanicolaou et al [4] and earlier by another researchers may be explained in two ways. First, the content of soil solution was determined there by the chemical analysis of soil, but not by the direct measurement of soil solution.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…This question should be investigated additionally in more details. We think that the difference in the ratios strontium-calcium in plant and in the corresponding soil solution marked by Papanicolaou et al [4] and earlier by another researchers may be explained in two ways. First, the content of soil solution was determined there by the chemical analysis of soil, but not by the direct measurement of soil solution.…”
Section: Resultsmentioning
confidence: 78%
“…This equality or OR-value should help to predict the uptake of strontium to plants. Other researchers disagree, however, with the above assertion (Papanicolaou et al [4]). They showed that the calculated OR-values varied considerably.…”
Section: Introductionmentioning
confidence: 89%